Spectrophotometric Studies of Complexes of Nickel(II) with 6-Substitued-1-Hydeoxy-1,2,3-Benzotriazoles Part-VII - Verma, B.B.; Singh, D.; Parmar, M.S. (Asian Journal of Chemistry, 2010)
Job´s method of continuous variation as well as molar ratio method have been used in order to establish the stoichiometry of complexes of nickel(II) with 6-substituted-1-hydroxy-1, 2, 3-benzotriazoles (6-Chloro-, 6-bromo and 6-nitro-1-hydroxy-1, 2.4-benzotriazole). The metal to ligand ratio is found to be 1 : 2. Stability constant of the order of 107 to 108. Free energy values of the complex formation are also given.